Epigenetic insights into physiological resilience: Multigenerational readouts of CO2-induced seawater acidification effects on fish embryos - Tzu-Yen Liu; Jia-Jiun Yan; Ying-Jey Guh; Oki Hayasaka; Li-Yih Lin; Pung-Pung Hwang; Guan-Chung Wu; Ming-Tsung Chung; Yung-Che Tseng (iScience)
Summary: Anthropogenic CO2 emissions are acidifying oceans, threatening marine organisms during early development. We investigated multigenerational effects of projected 2100 acidification (pH 7.6) on marine medaka (Oryzias melastigma) embryos across three generations using integrated phenotypic, physiological, transcriptomic, and epigenetic analyses. Prolonged acidification altered developmental trajectories, with F2 embryos showing size reductions. Metabolic responses were generation-specific: F0 embryos displayed decreased ammonium excretion, while F1 and F2 maintained stable profiles. Transcriptomic analysis revealed generational changes in neurotransmission, ion regulation, and epigenetic pathways. F2 embryos exhibited attenuated transcriptional perturbations and partial restoration of acid-base homeostasis, suggesting enhanced adaptability. Adaptive gene expression correlated with hypomethylation recovery of ion transport genes AE1a and NHE2 in F2 embryos. Increased hypomethylated AE1a promoter CpG sites in F1 and F2 generations aligned with elevated transcription, indicating epigenetically-driven enhancement. These results demonstrate epigenetic control’s crucial role in multigenerational plasticity and adaptive responses to ocean acidification.